VD_FINDINFO Décision / 2023 / 485 vom 21. Juni 2023 - VD Tribunal cantonal (2023)
DÉTENTION PROVISOIRE, PROPORTIONNALITÉ, PRINCIPE DE LA CÉLÉRITÉ, DURÉE, PROLONGATION | 212 al. 3 CPP (CH), 221 al. 1 let. a CPP (CH), 227 CPP (CH)